Central-line-associated Blood Stream Infections in Children Admitted to a South African Paediatric Intensive Care Unit - Nompumelelo Victoria Bobotyana; Nombini Pinkie Zozi; Siyazi Mda (Journal of Pediatric Emergency and Intensive Care Medicine)
Introduction: Central line associated bloodstream infection (CLABSI) is a common complication of venous access. Rates of CLABSI are reportedly higher in middle-income countries compared with high-income countries. There is a paucity of data concerning CLABSI in South Africa. In this study we aimed to assess the prevalence of CLABSI and its associated factors at Dora Nginza Hospital. Methods: We conducted a retrospective review of medical and laboratory records of all paediatric intensive care unit (PICU) patients who had central lines placed between January 2019 to December 2019. The CLABSI was defined according to Centers for Disease Control and Prevention guidelines. Eligible patients had to have had a central line for two days prior to CLABSI. Information concerning the type of the central line, associated factors, septic markers, and the organisms that were cultured was obtained from the records. Ethics approval was granted by the Institutional Review Board of Walter Sisulu University. Results: In all, 289 patients were admitted in PICU during the period of the study, and 131 had central lines. The files of 107 children were used for the study with a total of 598 catheter days. Among 107 participants 19 CLABSI were identified yielding a CLABSI rate of 31.7 per 1000 catheter days. Patients with CLABSI had more central line days than those who did not develop CLABSI (p<0.01). Blood transfusion was also a risk factor for CLABSI in this study. Other known risk factors like antibiotics, catheter site, total parenteral nutrition, malnutrition were not found to be significantly associated in this study. Causes of CLABSI were Gram-negative (n=10, 52%) being predominant, followed by fungal at (26%, n=5) and Gram-positive (n=3, 15.8%). Conclusion: The prevalence of CLABSI at Dora Nginza Hospital is high compared to rates reported in middle-income countries. Strict adherence to prevention bundles is required reduce CLABSI prevalence.